1983
DOI: 10.1002/jhet.5570200609
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of some benzimidazole‐ and benzothiazole‐derived ligand systems and their precursory diacids

Abstract: Procedures are described for the preparation of various bidentate and linear tetradentate benzimidazoles and benzothiazoles incorporating units such as pyridyl and thioether, and for the preparation of certain thioether dicarboxylic acids precursory to them. Condensations of ortho‐functinal anilines with carboxylic acids were carried out in polyphosphoric acid or refluxing HCl solution. Syntheses are reported for: [HO2C(CH2)2S(CH2)2]2X (X = O, S), 1,9‐bis(benzimidazol‐2‐yl)‐2,5,8‐trithianonane, 1,11‐bis(N‐meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
2

Year Published

1987
1987
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(44 citation statements)
references
References 21 publications
1
41
0
2
Order By: Relevance
“…Although the mono- [13,18,21,22] and di-benzothiazoline [27][28][29] analogs in the current study have been previously reported, much of the spectroscopic characterization is incomplete and 1 H NMR data is mostly unavailable. The lack of data could be the result of oxidation products forming in tandem with the desired product complicating the analyses.…”
Section: Synthesis and Characterization Of Benzothiazoline -Thiazolementioning
confidence: 90%
“…Although the mono- [13,18,21,22] and di-benzothiazoline [27][28][29] analogs in the current study have been previously reported, much of the spectroscopic characterization is incomplete and 1 H NMR data is mostly unavailable. The lack of data could be the result of oxidation products forming in tandem with the desired product complicating the analyses.…”
Section: Synthesis and Characterization Of Benzothiazoline -Thiazolementioning
confidence: 90%
“…The ligand bmbz was obtained as a byproduct and in low yield in an earlier attempt to synthesize the compound [15]. We have prepared bmbz with increased yield and in one step by the adaptation of the published procedures for N -methylbenzimidazoles and 2-arylbenzimidazoles [16,17] Then, the copper complex was prepared by slowly adding a solution of copper(II) triflate (1.2 mmol) in methanol to a stirred solution of the ligand (0.41 g, 1.2 mmol) in methanol. The reaction mixture was further stirred for 0.5 h, and on slow evaporation of the solvent, the copper complex crystallized as dark brownish green microcrystals [19].…”
mentioning
confidence: 99%
“…The solid product was filtered off and recrystallized from acetone [Fe(bzimpy À1H ) 2 ] AE H 2 O (4). The ligand bzimpy was prepared by procedures described elsewhere [9]. The solution I: 0.31 g (1.0 mmol) of bzimpy, 20 cm 3 of ethanol, and 2 cm 3 of water.…”
mentioning
confidence: 99%